Evaluation of Stability and Biological Activity of Solid Nanodispersion of Lambda-Cyhalothrin - Cui, Bo; Feng, Lei; Pan, Zhenzhong; Yu, Manli; Zeng, Zhanghua; Sun, Changjiao; Zhao, Xiang; Wang, Yan; Cui, Haixin (PLOS ONE, 2015)
Pesticides are essential agrochemicals used to protect plants from diseases, pests and weeds. However, the formulation defects of conventional pesticides cause food toxicity and ecological environmental problems. In this study, a novel, efficient and environmentally friendly formulation of lambda-cyhalothrin, a solid nanodispersion, was successfully developed based on melt-emulsification and high-speed shearing methods. The solid nanodispersion presented excellent advantages over conventional pesticide formulations in such formulation functions as dispersibility, stability and bioavailability. The formulation is free of organic solvents, and the use of surfactant is reduced. Therefore, the application of the solid nanodispersion in crop production will improve efficacy and reduce the occurrence of both pesticide residues in food and environmental pollution from pesticides.